The study of perspective medicinal plants using the example of Helianthus tuberosus L. - Utegalieva Tamila; Dukenbayeva Assiya; Ergazy Aida; Yessenova Gulden; Nurgabyl Altynay (BIO Web of Conferences, 2024)
This paper presents the results of microscopic analysis of a perspective medicinal plant Helianthus tuberosus used for the treatment of diabetes mellitus. The study was conducted to identify specific morphological and structural characteristics of this plant, which may have a positive impact on the efficacy and safety of its use for medical purposes. Different types of plant material were used in the research: fresh plants, dried plant material and preserved plant material. For preservation of the latter, a special mixture consisting of ethyl alcohol, glycerol and distilled water in equal volumes was used. Anatomical study of the structure and structure of plants was carried out using several methods: to study the structure of the epidermis, surface samples were prepared, which allowed us to get a detailed idea of the cellular composition and location of the epidermis on the surface of leaves, stems and roots of plants; for a deeper study of the internal structure of plants, transverse sections were made, which were further investigated. The results of the study suggest the high potential of this plant as a basis for the development of safe and effective phytopreparations.